Pendekatan Kualitatif Dalam Mengkaji Media Sosial Dan Pola Konsumsi Generasi Milenial - Defriyanti, Adela; Fitri, Nur Elisa (EL-EMIR Institute, 2024)
This study aims to investigate how social media influences the millennial generation's shopping tendencies. This generation is a major focus in modern consumption research due to their intense engagement on social media platforms and its impact on shopping decisions. Through qualitative methods, this research examines how the millennial generation's consumer behavior is influenced by social comparison. The results show that social media not only makes access to products and brands easier, but also strengthens consumption culture by promoting a certain lifestyle that often focuses on purchasing goods and services. Social media has had a huge impact on the way the millennial generation consumes goods and lifestyles. Through this platform, they are not only exposed to interesting products and consumption patterns, but are also influenced by trends and recommendations from other users. Social media facilitates product comparison, review searches, and easy online shopping, which can encourage impulsive consumer behavior. Additionally, constant exposure to content that promotes a materialistic lifestyle can influence spending priorities and result in increased consumption of items that may not always be necessary. This is a challenge for millennials in managing finances wisely and adjusting consumption patterns to actual needs.